Delineation of dominant and recessive forms of LZTR1‐associated Noonan syndrome. Issue 6 (3rd April 2019) - Pagnamenta, Alistair T.; Kaisaki, Pamela J.; Bennett, Fenella; Burkitt‐Wright, Emma; Martin, Hilary C.; Ferla, Matteo P.; Taylor, John M.; Gompertz, Lianne; Lahiri, Nayana; Tatton‐Brown, Katrina; Newbury‐Ecob, Ruth; Henderson, Alex; et al.
Abstract : Noonan syndrome (NS) is characterised by distinctive facial features, heart defects, variable degrees of intellectual disability and other phenotypic manifestations. Although the mode of inheritance is typically dominant, recent studies indicate LZTR1 may be associated with both dominant and recessive forms. Seeking to describe the phenotypic characteristics of LZTR1‐ associated NS, we searched for likely pathogenic variants using two approaches. First, scrutiny of exomes from 9624 patients recruited by the Deciphering Developmental Disorders (DDDs) study uncovered six dominantly‐acting mutations (p.R97L; p.Y136C; p.Y136H, p.N145I, p.S244C; p.G248R) of which five arose de novo, and three patients with compound‐heterozygous variants (p.R210*/p.V579M; p.R210*/p.D531N; c.1149+1G>T/p.R688C). One patient also had biallelic loss‐of‐function mutations in NEB, consistent with a composite phenotype. After removing this complex case, analysis of human phenotype ontology terms indicated significant phenotypic similarities ( P = 0.0005), supporting a causal role for LZTR1 . Second, targeted sequencing of eight unsolved NS‐like cases identified biallelic LZTR1 variants in three further subjects (p.W469*/p.Y749C, p.W437*/c.‐38T>A and p.A461D/p.I462T). Our study strengthens the association of LZTR1 with NS, with de novo mutations clustering around the KT1‐4 domains. Although LZTR1 variants explain 0.1% of cases across the DDD cohort, the gene is a relatively common cause of unsolved NS cases where recessive inheritance is suspected. Abstract :